Kunjungan dan Pembentukan Pojok Literasi di Yayasan Panti Asuhan Bina Ummah Doktor Haji Adamri Al Husany - Jimmy Lee; Fadhilah Insani Liesvy Turrina; Jeffri Liu; Laely Aribah Istiqomah; Christine Stefani; Verin Stefania Huang; Windi Eka Putri; Joenne Joenne; Suci Changyoni Putri; Vallen Angellito; Wilson Wilson; Daren Daren; Joanna Joanna; Gary Tanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Literacy is a quality or ability to be literate/literate which includes the ability to read and write. At present, the literacy level of the Indonesian people is of concern nationally, even internationally, where its position is quite lagging behind. Lazy reading behavior can threaten the survival and future of the Indonesian nation. All levels of society, starting from families, educational institutions, to government institutions must actively participate in succeed the Literacy Movement in Indonesia. Children of the Bina Ummah Doctor Haji Adamri Al Husany Orphanage Foundation in particular as partners in our Humanity Project implementation activities to jointly strive to realize the “Gerakan Gemar ke Perpustakaan (Gempusta)”. Data collection techniques using mixed methods, which are divided into 50% qualitative methods and 50% quantitative methods. Qualitative methods come from literature reviews such as journals, articles and other reading materials. While the quantitative method comes from data obtained through surveys conducted by means of observation and interviews. The results obtained after implementing the service, namely the Children of the Bina Ummah Doctor Haji Adamri Al Husany Orphanage Foundation can develop and their knowledge of the importance of literacy, make literacy a good habit every day in supporting the Gerakan Literasi Sekolah (GLS), and maximize knowledge about waste/3R (Reduce, Reuse, Recycle) about waste.